Aflatoxin-producing fungi associated with pre-harvest maize contamination in Uganda - Sserumaga, J.P.; Ortega Beltran, A.; Wagacha, J.M.; Mutegi, C.K.; Bandyopadhyay, Ranajit (Elsevier, 2020)
Maize is an important staple crop for the majority of the population in Uganda. However, in tropical and subtropical climates, maize is frequently contaminated with aflatoxins, a group of cancer-causing and immuno-suppressive mycotoxins produced by Aspergillus section Flavi fungi. In Uganda, there is limited knowledge about the causal agents of aflatoxin contamination. The current study determined both the aflatoxin levels in pre-harvest maize across Uganda and the structures of communities of aflatoxin-producing fungi associated with the maize. A total of 256 pre-harvest maize samples were collected from 23 major maize-growing districts in eight agro-ecological zones (AEZ). Maize aflatoxin content ranged from 0 to 3,760 ng/g although only around 5% of the samples contained aflatoxin concentrations above tolerance thresholds. A total of 3,105 Aspergillus section Flavi isolates were recovered and these were dominated by the A. flavus L morphotype (89.4%). Densities of aflatoxin-producing fungi were negatively correlated with elevation. Farming systems and climatic conditions of the AEZ are thought to have influenced communities’ structure composition. Fungi from different AEZ varied significantly in aflatoxin-producing abilities and several atoxigenic genotypes were identified. The extremely high aflatoxin concentrations detected in some of the studied regions indicate that management strategies should be urgently designed for use at the pre-harvest stage. Atoxigenic genotypes detected across Uganda could serve as aflatoxin bio-control agents to reduce crop contamination from fields conditions and throughout the maize value chain.